Promoting conceptual change of learning sorting algorithm through the diagnosis of mental models: The effects of gender and learning styles - Lau, Wilfred W.F.; Yuen, Allan H.K. (Computers and education, 2010)
It has been advocated that pedagogical content knowledge as well as subject matter knowledge are important for improving classroom instructions. To develop pedagogical content knowledge, it is argued that understanding of students’ mental representations of concepts is deemed necessary. Yet assessing and comparing mental model of each individual is very tedious and time consuming. This study attempted to use gender and learning styles to associate mental models in learning sorting algorithm. The Gregorc Style Delineator (GSD) was used to measure learning styles of the participants. Mental models were assessed using the Pathfinder Scaling Algorithm (PSA). Results indicated that females showed greater similarity in mental models than males and concrete learners also exhibited closer resemblance to the expert mental model than abstract learners. These suggest that gender and learning styles can be meaningfully used to associate mental models in order to provide a group-based instead of individual-based diagnosis and thus promote conceptual change in learning.